An Interview About Maraboutism And Evil Spirits (NCAC_RDD_TAPE_0782A_B) - Boojang, Sirifu; Nyandu, Alhaji Mfaamara Omaar (Universität Hamburg, 2023)
Continuation of TAPE_0781;- Prediction;- Maraboutism;- Types of Marabouts;- Evil spirits (jina);- Satan;Alternative names: Alhagie, Alhagi, Nfamara, Mfamara Oumar, Omar, Bojang, Sirifo, Sherifo, Sherriffo, Sherrifo, Shirifu